Real stories of small business success : successful, small scale, manufacturing from five European island regions : a training manual - Baldacchino, Godfrey; European Commission. Leonardo da Vinci Community Vocational Training Action Programme (European Commission, 2005)
The support of the European Commission, through its Leonardo da Vinci Community Vocational Training Action Programme, in this ongoing pilot project- MT/2002/B/F/139000- is gratefully acknowledged. This manual has been compiled by University of Malta Professor Godfrey Baldacchino (the NISSOS Project ideator and academic coordinator) with the kind support of the project’s 11 institutional partners, their delegates and associated support staff involved in the NISSOS Project. These are: Estonia Chamber of Commerce and Industry-Saaremaa Branch (Delegate: Tullio Liblik); Kuressaare College at Tallinn Technical University (Maret Pank); Åland Trade Association (Mika Lindfors & Johnny Mattson); Åland Polytechnic (Anna-Lena Freman, Christer Kullman & Thor-Bjorn Wik); Technological Institute of Iceland (Bjorn Gislason); Institute of Business Studies at the University of Iceland (Gylfi Dalmann Adalsteinsson); Foundation for Human Resources Development, Malta (Helga Ellul, Mario Grixti, Godwin Micallef, John Muscat Drago); Malta Enterprise (Karl Herrera); University of Malta (Roger Ellul Micallef, Saviour Rizzo); Malta College for Arts, Science and Technology (Frank Edwards); the Highland Council of Scotland (Catriona Maclean; Lisa Stephen) and the UHI Millennium Institute, Scotland (Maggie Marr; Anne Marie McDairmid, Stephanie Tristam). Thanks also to the expert independent input of Joe Vella Bonnici (Malta), Ingi Runar Edvardsson (Iceland) and Tage Petersen (Denmark). The institutional support of the University of Prince Edward Island, Canada, is also acknowledged. Responsibility for the contents of this manual and any errors are those of the author and are not attributable to the European Commission or any of the specific NISSOS Project institutional partners. It is common knowledge nowadays that small and medium sized enterprises (SMEs) are very important to economic growth. Their positive contribution is all the more evident in the context of massive lay-offs from large firms and especially appreciated in epochs of long term, structural unemployment. SMEs play an even more pronounced role in the case of very small islands, since the typical average enterprise size is even smaller than elsewhere. Manufacturing is also seen as an important contributor to economic growth and development. The factory has been a symbol of industrial progress for the last 200 years. Manufacturing creates many jobs, usually in large firms, develops technical skills, adds higher value to products and creates many supportive service industries. However, many handicaps can affect the set-up and operation of SMEs which are based in small island territories And are involved in manufacturing. How challenging are these handicaps? Can they be overcome? How? Can some small firms from small islands serve as models of successful export-oriented development? And if so, which? What would be their characteristics? peer-reviewed